A STUDY OF THE PENETRATION OF MAMMALIAN CELLS BY DEOXYRIBONUCLEIC ACIDS - Borenfreund, Ellen (The Rockefeller University Press, 1961)
Tritium-labeled deoxyribonucleic acid (DNA) from pneumococci and from human leukocytes was added to growing cultures of HeLa cells at 37°C. Autoradiography revealed an extensive localization of tritium in the nuclear regions. The label could not be removed by treatment with ribonuclease or dilute perchloric acid, but quantitative removal from the cells could be effected with deoxyribonuclease. Chemical and radioactivity determinations on nucleic acids isolated from the exposed HeLa cells revealed the presence of tritium in all 4 DNA bases. About 12 µg. of tritiated DNA was recovered from 6 x 10(6) HeLa cells which had been exposed for 24 hours to 240 µg. of the human DNA. From this, it is concluded that the amount of DNA, or its degradation products, taken up by the cells was equivalent to at least 10 per cent of the normal HeLa cell complement.